Comparative Genomic Analyses and CRISPR-Cas Characterization of Cutibacterium acnes Provide Insights Into Genetic Diversity and Typing Applications - Cobian, Natalia; Garlet, Allison; Hidalgo-Cantabrana, Claudio; Barrangou, Rodolphe (Frontiers in Microbiology, 2021)
Cutibacterium acnes is an important member of the human skin microbiome and plays a critical role in skin health and disease. C. acnes encompasses different phylotypes that have been found to be associated with different skin phenotypes, suggesting a genetic basis for their impact on skin health. Here, we present a comprehensive comparative analysis of 255 C. acnes genomes to provide insights into the species genetic diversity and identify unique features that define various phylotypes. Results revealed a relatively small and open pan genome (6,240 genes) with a large core genome (1,194 genes), and three distinct phylogenetic clades, with multiple robust sub-clades. Furthermore, we identified several unique gene families driving differences between distinct C. acnes clades. Carbohydrate transporters, stress response mechanisms and potential virulence factors, potentially involved in competitive growth and host colonization, were detected in type I strains, which are presumably responsible for acne. Diverse type I-E CRISPR-Cas systems and prophage sequences were detected in select clades, providing insights into strain divergence and adaptive differentiation. Collectively, these results enable to elucidate the fundamental differences among C. acnes phylotypes, characterize genetic elements that potentially contribute to type I-associated dominance and disease, and other key factors that drive the differentiation among clades and sub-clades. These results enable the use of comparative genomics analyses as a robust method to differentiate among the C. acnes genotypes present in the skin microbiome, opening new avenues for the development of biotherapeutics to manipulate the skin microbiota.